2019
DOI: 10.2478/aiht-2019-70-3211
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of exhaled breath temperature after smoking a cigarette and its association with lung function changes predictive of COPD risk in smokers: a cross-sectional study

Abstract: Exhaled breath temperature (EBT) is a biomarker of inflammation and vascularity of the airways already shown to predict incident COPD. This cross-sectional study was aimed to assess the potential of EBT in identifying “healthy” smokers susceptible to cigarette smoke toxicity of the airways and to the risk of developing COPD by analysing the dynamics of EBT after smoking a cigarette and its associations with their demographics (age, smoking burden) and lung function. The study included 55 current smokers of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…A recent study showed that smokers have a full one degree C elevated breath temperature compared to non-smokers. 55 Furthermore, in the hour after a cigarette is smoked breath temperature is further increased by an average of .42 degrees C. Smokers are chronically experiencing a localized relative heating of the respiratory tract, believed to be principally related to increased blood flow associated with inflammation. 56 To the extent that temperature is implicated in a smoker's physiology, it is reasonable to consider that there are a host of much more benign ways to warm the respiratory tract than smoking.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that smokers have a full one degree C elevated breath temperature compared to non-smokers. 55 Furthermore, in the hour after a cigarette is smoked breath temperature is further increased by an average of .42 degrees C. Smokers are chronically experiencing a localized relative heating of the respiratory tract, believed to be principally related to increased blood flow associated with inflammation. 56 To the extent that temperature is implicated in a smoker's physiology, it is reasonable to consider that there are a host of much more benign ways to warm the respiratory tract than smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this hypothesis, smoking can increase the temperature of the respiratory tract by an average of 1.25°C. This was determined by measuring the 5-minute post-smoking exhaled breath temperature [ 48 ], a variable with 98% specificity for predicting future development of COPD in smokers [ 4 ]. It is, however, unclear whether this rise of 1.25°C in temperature might be sufficient to induce promoter-specific H3K27me3 enrichment in certain genes, such as IL-6, in the epithelial cells of the respiratory tract.…”
Section: Smoking Instigates Inflammation In Covid-19 By Inducing Il-6 Il-17 and Pge2mentioning
confidence: 99%